Toxicity of metal–organic framework nanoparticles: from essential analyses to potential applications. (5th January 2022) - Ettlinger, Romy; Lächelt, Ulrich; Gref, Ruxandra; Horcajada, Patricia; Lammers, Twan; Serre, Christian; Couvreur, Patrick; Morris, Russell E.; Wuttke, Stefan
Abstract : This tutorial review highlights the key aspects of nanotoxicity and the importance of its systematic assessment for metal–organic framework (MOF) nanoparticles to pave the way towards their potential applications in a safe and sustainable manner. Abstract : In the last two decades, the field of metal–organic frameworks (MOFs) has exploded, and MOF nanoparticles in particular are being investigated with increasing interest for various applications, including gas storage and separation, water harvesting, catalysis, energy conversion and storage, sensing, diagnosis, therapy, and theranostics. To further pave their way into real-world applications, and to push the synthesis of MOF nanoparticles that are 'safe-and-sustainable-by-design', this tutorial review aims to shed light on the importance of a systematic toxicity assessment. After clarifying and working out the most important terms and aspects from the field of nanotoxicity, the current state-of-the-art of in vitro and in vivo toxicity studies of MOF nanoparticles is evaluated. Moreover, the key aspects affecting the toxicity of MOF nanoparticles such as their chemical composition, their physico-chemical properties, including their colloidal and chemical stability, are discussed. We highlight the need of more targeted synthesis of MOF nanoparticles that are 'safe-and-sustainable-by-design', and their tailored hazard assessment in the context of their potential applications in order to tap the full potential of this versatile material class in the future.